Violence against resident doctors, its psychological impact and associated factors in accident & emergency department in a tertiary care institute of Haryana - Vaishali, Vaishali; Chayal, Vinod; verma, Ramesh; Khanna, Pardeep (Indian Journal of Community Health, 2018)
Background: Violence in the healthcare setting is very common with the emergency department (ED) having the highest rate of violence in the hospital. While on one hand, the physical violence at the workplace has always been well recognized, the existence of psychological violence has been long underestimated. Materials and Methods: The study was a descriptive type of cross-sectional study conducted in 6 months in a tertiary care center of Haryana among doctors in Emergency and casualty Department. Study subjects were junior residents and senior residents posted in the emergency department. The questionnaire is a predesigned survey questionnaire formulated by ILO/ ICN/ WHO/ PSI Joint. Results: Most of the physical violence was seen in Surgery & Orthopaedics department with respective frequency of 44% & 39% respectively; while most of the verbal abuse reported in Medicine department with frequency of 33%. Most of the physical violence and verbal abuse occurred in age group of 25-29; males were more predisposed to both physical and psychological violence. Only 63% of the subjects knew about the procedures of reporting existing in the health facility. Conclusion: The study concludes that physical violence and verbal abuse are high in our institute, but majority of doctors did not know about the procedures of reporting.